Evaluation of Woodball Achievement Coaching Management - Agus Supriyanto; Wawan Sundawan Suherman; Erwin Setyo Kriswanto; Yudik Prasetyo; Ahmad Nasrulloh; Danny Eka Wahyu Saputra; Sugeng Setia Nugroho; Dewangga Yudhistira (Jorpres (Jurnal Olahraga Prestasi), 2023)
This study aims to determine the results of the evaluation of the context, input, process, and product management of the Yogyakarta Special Region of Woodball. The evaluation model that will be used in this study is the CIPP model. The data analysis technique in this research is quantitative and qualitative descriptive analysis. Results: The results showed that the evaluation of the Yogyakarta Special Region Woodball sport of 2.65 was in the good category. (1) The context of the evaluation of the Yogyakarta Special Region Woodball sports management, amounting to 3.12 is in the good category. Based on the background indicators for the coaching program, 3.23 in the good category, the goal of the coaching program in the 3.00 in the good category, and the coaching program in the 3.14 in the good category. (2) The input for evaluation of the Yogyakarta Special Region Woodball sports management, amounting to 2.40 is in the less category. Based on the indicators of human resources of 2.57 good categories, the trainer program is 2.48 poor categories, 2.31 poor categories, facilities and infrastructure are 2.35 poor categories, and parental support is 2.31 less categories. (3) The evaluation process of the Yogyakarta Special Region Woodball sports management, amounting to 2.59 is in the good category. (4) Evaluation of the Yogyakarta Special Region Woodball sports management product, amounting to 2.49 is in the poor category. The evaluation of the management of woodball achievement development in Yogyakarta Province went well, with all factors investigated yielding positive results.